Effects of BRAC's development inputs on women's lives - Huda, Samiha; Khan, Mahmuda Rahman; Mahmud, Simeen; Khan, Shahriar Reza; Chowdhury, Mushtaque; Bhuiya, Abbas; Khan, Munirul Islam (BRAC Research and Evaluation Division (RED), 2019)
The BRAC-ICDDR,B Joint Research Project consists of two phases of research, analysis and interpretation over a 6-year project cycle. Initiated in 1992, research in Phase I (1992- 1995) involved a large cross-sectional survey and a series of exploratory studies to assess existing differences in the population prior to BRAC's RDP intervention. These studies sought to elucidate the socioeconomic and environmental context within which BRAC's programmes would operate. Informed by the baseline and exploratory studies referred to above, the Currently operating Phase n of this project (1995-1998) involves both in-depth and longitudinal investigations of the hypotheses generated during Phase I. This report documents the health component of the first of the three rounds of longitudinal data collected during summer, rainy and dry seasons respectively beginning the middle of April 1995.